Computational Study of the Stability of Tautomers and equilibrium constants of Cyanuric acid (CA) in Different solvents. - Babu, Numbury Surendra; Jayaprakash, Didugu (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
In the present investigation, the tautomeric and equilibrium of Cyanuric acid has been studied using Hartifock (HF) method in the gas phase and different solvents using the PCM model. The relative energies of these tautomers have been calculated at the HF level of theory using 6-311++ G (d,p) basis set. Energetics and relative stabilities of the tautomers were compared and analyzed in both the gaseous and different solvents. The results indicate that the keto tautomer (CA1) is the most stable form in the gas phase and other solvents. The order of stability of isomers was found to be CA1 > CA3> CA11> CA2> CA6> CA10> CA7> CA4> CA5> CA9>CA8. Having the largest dipole moment the CA8 tautomer is expected to have the strongest interaction with polar solvents. The HF method calculated tautomeric equilibrium constants with respect to the most stable tautomer CA1 of Cyanuric acid both in the gas and in different solvents. The of the equilibrium constants calculated starting from the general outline of interconversion.